Pengaruh Gamifikasi Berbasis Literasi Digital Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Atika, Afifah Nur; Purbosari, Para Mitta (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
This research is motivated by the low critical thingking skills of elementary school students and the suboptimal utilization of learning technology, where teachers tend to only use technology as a medium for delivering material. This study aims to examine the effect of digital literacy-based gamification on the critical thingking skills of students at SD Negeri Jombor 01, Sukoharjo. This study uses a quantitative approach with a quasi-experimental design. The sample of this study involved two classes, namely class VA as an experimental class that received digital literacy-based gamification treatment, and class VB as a control class that used LKPD as a printed media in the learning process. The data collection technique used a multiple-choice test of 15 questions to measure critical thingking variables. The results of the study indicate that there is an influence of digital literacy-based gamification on students’ critical thingking skills. It can be concluded that the use of digital literacy-based gamification is significantly effective in strengthening the cognitive processes and critical thingking skills of elementary school students in facing the challenges of 21 st-century education.